1983
DOI: 10.1104/pp.73.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Studies of Nitrate Uptake into Barley Plants Using Ion-Specific Electrodes and 36ClO3

Abstract: The influence of NH4', in the external medium, on fluxes of NO3-and K were investigated using barley (Hordeum vulgare cv Betzes) plants.NWV was without effect on NO3-(3'10C3-) influx whereas inhibition of net uptake appeared to be a function of previous N03-provision. Plants grown at 10 micromolar NO3-were sensitive to external NHW when uptake was measured in 100 micromolar NO3-. By contrast, NO3-uptake (from 100 micromolar NO3-) by plants previously grown at this concentration was not reduced by NI-14 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…Net flux of NO3-remained relatively unchanged when Prato barley seedlings were supplied both NO3-and NH4+ at 200 ,uM. This is in contrast to the reports in the literature of significant reductions in NO3-net flux in the presence of NH4+ (5,7,13).…”
Section: Selectivitycontrasting
confidence: 87%
See 1 more Smart Citation
“…Net flux of NO3-remained relatively unchanged when Prato barley seedlings were supplied both NO3-and NH4+ at 200 ,uM. This is in contrast to the reports in the literature of significant reductions in NO3-net flux in the presence of NH4+ (5,7,13).…”
Section: Selectivitycontrasting
confidence: 87%
“…9A) Many reports have appeared in the literature concerning the influence of ammonium on nitrate uptake in barley (3,5,7,13), maize (14,16,23), and tomato (24). Deane-Drummond and Glass (5) have suggested that the influence of ammonium on nitrate net uptake depends on the amount of nitrate previously available. Using 36C103-as an analog for NO3-, nitrate influx from a solution of 100 Mm NO3-was not affected by the presence of 100 to 500 Mm NH4+ ifthe seedlings had been previously grown at that nitrate concentration.…”
Section: Selectivitymentioning
confidence: 99%
“…N efflux (either NH4+ or NO3-) has been reported to be quite significant, particularly at elevated concentrations of N (Morgan et al, 1973;Breteler and Nissen, 1982). Indeed, Deane-Drummond and Glass (1983aGlass ( , 1983b suggested that nitrate efflux might regulate net uptake by means of a type of pump and leak mechanism. By contrast, Lee and colleagues have emphasized the importance of influx in the regulation of net uptake of nitrate, although nitrate efflux was equivalent to almost 40% of nitrate influx in barley roots (Lee and Clarkson, 1986;Lee and Drew, 1986).…”
Section: Fluxes Of 13nh+ Into Root Cellsmentioning
confidence: 99%
“…According to Deane-Drummond and Glass (6,7) and Glass (10), who used 36C103-and '3NO3-, respectively, to examine NO3-influx after various NO3-pretreatments, influx was independent of prior exposure to NO3-. By contrast, Lee and Drew (17) showed that withholding NO3-for 3 d increased Vma for NO3-influx.…”
mentioning
confidence: 99%